Bold Ventures Volume 1
XVIII, 250 p. 2 illus.
Keywords: This book, based on detailed studies of eight innovations in mathematics and science education, has many insights to offer on current school reform. Since each innovation studied has taken its own unique approach, the set as a whole spans the spectrum from curriculum development to systemic reform, from con centrating on particular school populations to addressing all of K-12 education. Yet these reform projects share a common context, a world view on what mat ters in science and mathematics for students of the 1990s and beyond, convic tions about what constitutes effective instruction, and some notions about how school change can be brought about. These commonalities are drawn out in the book and illustrated with examples from the individual case studies that are reported in full in Bold Ventures, Volumes 2 and 3. The eight innovations-all of them projects that are well-known, at least by name, to U. S. audiences-are briefly described in chapter 1. Each was the sub ject of an in-depth, three-year case study. The research teams analyzed many documents, attended numerous project meetings, visited multiple sites, conduct ed dozens of individual interviews. The team leaders, having spent much time with mathematics or science education over long careers, looked at these reform projects through several lenses; the teams sifted through the mountains of data they had collected in order to tell the story of each project in rich detail.